의료기관 내 영상의학 검사 장비의 표면 오염도 분석 연구 - 이신우; Shin-woo Lee; 김다은; Da-eun Kim; 문채원; Chae-won Mun; 김갑중; Gap-jung Kim; 김상하; Sang-ha Kim; 박혜미; Hye-mi Park; et al. (한국방사선학회 논문지, 2024)
본 연구에서는 대전지역 종합병원 중 일반촬영장치, CT, MRI 검사 장치 각 2대씩 선정하여 시간대 별 검사 장치의 표면오염도를 측정하여 감염도를 예측하고 감염 예방을 위한 기초자료로 활용하고자 실험을 하였다. 그 결과 일반촬영장치와 MRI 검사장치의 시간대 별 표면 오염도는 13시>8시>16시 순이였으며, CT검사 장치는 13시>16시>8시 순이었으며 이는 검사 건수의 영향으로 나타났다. 또한 검사 장치 부위 별 표면오염도 결과는 일반촬영장치는 Stand Bucky 손잡이, CT 검사장치는 머리받침대, MRI 검사 장치는 조작 스위치에서 ATP 오염도 수치가 가장 많이 나왔으며, 이는 접촉 건수와 밀접한 관계가 있었다. 소독 전후를 비교한 결과 소독 후 모든 장치에서 유의한 차이로 감소한 결과를 보였다. 실험 결과를 바탕으로 영상의학과 검사실의 오염도를 파악하고 감염질환을 예방할 수 있는 기초자료가 될 수 있을 것이라고 사료된다. In this study, two general X-ray device, CT, and MRI inspection devices were selected from general hospitals in the Daejeon area and an experiment was conducted to predict the level of infection by measuring the surface contamination of the inspection devices at different times and to use it as basic data for infection prevention. As a result, the surface contamination level by time zone for general X-ray devices and MRI examination devices was in the order of 13H > 8H > 16H, and for CT examination devices, it was 13H > 16H > 8H, which appeared to be influenced by the number of tests. In addition, the surface contamination results for each part of the test device showed that the highest ATP contamination value was found on the stand bucky handle for the general X-ray device, the headrest for the CT examination device, and the operation switch for the MRI examination device, which was closely related to the number of contacts. As a result of comparing before and after disinfection, all devices showed a significant decrease after disinfection. Based on the results of the experiment, it is believed that it can be used as basic data to identify the level of contamination in radiology laboratories and prevent infectious diseases.